Bioengineered in vitro enteric nervous system. (22nd July 2019) - Manousiouthakis, Eleana; Chen, Ying; Cairns, Dana M.; Pollard, Rachel; Gerlovin, Kaia; Dente, Michael J.; Razavi, Yasmin; Kaplan, David L.
Abstract: Bidirectional interactions between the human central nervous system and the gastrointestinal tract, via the enteric nervous system, are unmapped and central to many human conditions. There is a critical need to develop 3D human in vitro intestinal tissue models to emulate the intricate cell interactions of the human enteric nervous system within the gastrointestinal tract in order to better understand these complex interactions that cannot be studied utilizing in vivo animal models. In vitro systems, if sufficiently replicative of some in vivo conditions, may assist with the study of individual cell interactions. Here, we describe a 3D‐innervated tissue model of the human intestine consisting of human‐induced neural stem cells differentiated into relevant enteric nervous system neural cell types. Enterocyte‐like (Caco‐2) and goblet‐like (HT29‐MTX) cells are used to form the intestinal epithelial layer, and intestinal myofibroblasts are utilized to simulate the stromal layer. In vitro enteric nervous system cultures supported survival and function of the various cell types, with mucosal and neural transcription factors evident over 5 weeks. The human‐induced neural stem cells migrated from the seeding location on the peripheral layer of the hollow scaffolds toward the luminal epithelial cells, prompted by the addition of neural growth factor. nNOS‐expressing neurons and the substance P precursor gene TAC1 were expressed within the in vitro enteric nervous system to support the utility of the tissue model to recapitulate enteric nervous system phenotypes. This innervated tissue system offers a new tool to use to help in understanding neural circuits controlling the human intestine and associated communication networks.